Pulmonary mixed squamous cell and glandular papilloma in the elderly: a case report and literature review - Zhang, Panpan; Wang, Yuan; Huang, Chao; Ji, Yanyan; Han, Xiaoqing (Frontiers in Oncology, 2025)
Mixed squamous cell and glandular papilloma (MSCGP) is a rare benign lung tumor, which mostly occurs in the central airway and primarily affects middle-aged and elderly individuals. Due to the limited understanding of the clinical characteristics of elderly patients, clinicians often lack a comprehensive grasp of MSCGP, leading to misdiagnosis. Therefore, in this article, we report a case of an elderly patient with central MSCGP and provide a comprehensive review of the relevant literature on elderly patients with MSCGP, aiming to improve the diagnostic rate of this disease.